Timing, mantle source and origin of mafic dykes within the gravity anomaly belt of the Taihang-Da Hinggan gravity lineament, central North China Craton. (September 2017) - Liu, Shen; Feng, Caixia; Feng, Guangying; Xu, Mengjing; Coulson, Ian M.; Guo, Xiaolei; Guo, Zhuang; Peng, Hao; Feng, Qiang
Highlights: Late Mesozoic mafic dykes in the Taihang-Da Hinggan Mountains, central North China Craton were dated at 122–132 Mas. The dykes were derived from enriched lithospheric mantle source. The origin of the dykes is related to the foundered lower crust, and the dykes were derived from partial melting of hybrid mantle source. Abstract: Six mafic dyke swarms crop out in Hebei Province within the Taihang-Da Hinggan gravity lineament magmatic belt, China, and were sampled. Here, we present new zircon laser ablation-inductively coupled plasma-mass spectrometry U-Pb age, whole rock geochemical, and Sr-Nd-Pb-Hf isotopic data for the six areas where these mafic dykes occur. The mafic (dolerite) dykes formed between 131.6 ± 1.6 and 121.6 ± 1.1 Ma, and are enriched in the light rare earth elements (LREE), some of the large ion lithophile elements (LILE; e.g., Rb, Ba, and Sr) and Pb, and are depleted in Th, U, Nb and Ta; some samples are also depleted in Eu. The dykes have high initial 87 Sr/ 86 Sr ratios (0.7055–0.7057), negative εNd (t) values (−12.5 to −11.9), relatively constant Pb isotopic ratios (( 206 Pb/ 204 Pb)i = 16.45–16.51, ( 207 Pb/ 204 Pb)i = 15.44–15.51, ( 208 Pb/ 204 Pb)i = 36.49-36.53), negative εHf (t) values (−18.2 to −15.1), and old Nd (T Nd DM2 ; 2.17–2.47 Ga) and Hf (T Hf DM2 ; 2.28–2.33 Ga) model ages. These geochronological, geochemical, and isotopic data indicate that the dykes were derived from magmas generated by low to moderate degree partial melting (1.0%–10%) of an EM1-like garnet lherzolite mantle source; these magmas fractionated olivine, clinopyroxene, and hornblende prior to emplacement, and assimilated minimal amounts of crustal material. Several possible models have previously been proposed to explain the origin of Mesozoic magmatism in this region. However, here we propose a foundering model for these studied mafic dykes, involving the foundering of eclogite from thickened lower crust due to the collision between the Siberian Craton and the North China Craon.